ROR promotes the proliferation and migration of esophageal cancer through regulating miR-145/LMNB2 signal axis - Su, Xiangyu (Am J Transl Res, 2020)
Objective: LMNB2 is a protein that belongs to the RAB family. It is correlated with the tumorigenesis and development of several human cancers. The effect of LMNB2 on esophageal cancer (EC) has not yet been reported. The previous study showed that lncRNA ROR could promote the proliferation of EC. The current study aimed at exploring the correlation between ROR with LMNB2 and the role of ROR and LMNB2 in proliferation and migration of EC. Methods: This study performed dual luciferase reporter assay to evaluate the binding between miR-145 and ROR as well as miR-145 and LMNB2. Gene expression in EC tissues and cells were detected using quantitative real-time PCR (qRT-PCR) assay. The effect of ROR or miR-145 on LMNB2 expression was detected using western blot (WB) assay. Cells proliferation was detected by CCK8 and clone formation assay. Transwell and wound healing assay were carried out to determine the cells migration. Mouse xenograft assay was performed to detect the effect of LMNB2 on tumor growth in vivo. Results: This study demonstrated that miR-145 directly targets ROR and LMNB. ROR and LMNB2 were up-regulated and miR-145 was down-regulated in EC tissues and cells. The proliferation and migration of EC cells were promoted by overexpression of of ROR or LMNB2. MiR-145 was capable of reversing the effect of ROR. The results also determined that down-regulation of LMNB2 had inhibitory effects and up-regulation of LMNB2 had catalytic effects on tumor growth in vivo. Conclusion: LMNB2 which is regulated by ROR and miR-145 was highly expressed in EC and promoted the proliferation and migration of EC in vitro and in vivo. The study suggests that ROR and LMNB2 could be potentially the therapeutic targets of EC.